(untitled) (Eurasian Journal of History, Geography and Economics, 2021)
China is one of the most important emerging international powers and one of the poles of the new multipolar international system. China has adopted a clear and stable policy on the African continent for fifty years in an attempt to present itself as one of the developing third world countries to obtain a foothold in the African continent, which has succeeded in consolidating it through its constant willingness to help independent countries consolidate this independence. China has focused on its relations with Africa on establishing many significant projects and developing infrastructure to serve the countries of the African continent.